ADVANTAGES AND LIMITATIONS OF THE USE OF ACE INHIBITORS - Alibasic, Esad; Ljuca, Farid; Ramic, Enisa; Bajraktarevic, Amila; BaticMujanovic, Olivera; Dzafic, Fejzo; Zildzic, Muharem (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
Analysis of advantages and limitations in the application of ACE inhibitors. Background: ACEI are most frequently used group of antihypertensives. The mechanism of action of ACEI is such an act who works on modulating the renin-angiotensin-aldosterone system (RAAS). By blocking the angiotensin converting enzyme, ACEI significantly block the conversion of angiotensin I to angiotensin II. At the same time, reduce the degradation of bradykinin ACEI. Like any group of antihypertensive drugs, ACEI have some advantages and limitations (eg. Tolerability, side effects, cost) that can be critical for a decision on the application in an individual patient. Application of ACEI has priority code: subclinical organ damage (left ventricular hypertrophy, asymptomatic atherosclerosis, microalbuminuria, renal dysfunction), clinical events (previous stroke, previous myocardial infarction, heart failure, recurrent atrial fibrillation, renal failure / proteinuria), certain conditions (metabolic syndrome, diabetes). Restrictions or possible side effects of ACEI are cough, hyperkalemia, headache,